Consensus for Statements Regarding a Definition for Spinal Osteoarthritis for Use in Research and Clinical Practice: A Delphi Study. Issue 5 (18th January 2023) - de Luca, Katie; Chiarotto, Alessandro; Cicuttini, Flavia; Creemers, Laura; de Schepper, Evelien; Ferreira, Paulo H.; Foster, Nadine E.; Hartvigsen, Jan; Kawchuk, Gregory; Little, Christopher B.; Oei, Edwin H.; Suri, Pradeep; et al.
Abstract : Objective: To determine consensus among an international, multidisciplinary group of experts regarding definitions of spinal osteoarthritis for research and for clinical practice. Methods: A 15‐member, multidisciplinary steering committee generated 117 statements for a 3‐round Delphi study. Experts in back pain and/or osteoarthritis were identified and invited to participate. In round 1, participants could propose additional statements for voting. All statements were rated on a 1–9 Likert scale, and consensus was set at ≥70% of respondents agreeing or disagreeing with the statement and <15% of respondents providing the opposite response. Results: In total, 255 experts from 11 different professional backgrounds were invited. From 173 available experts, 116 consented to participate. In round 1, 103 participants completed the survey, followed by 85 of 111 participants in round 2 (77%) and 87 of 101 participants in round 3 (86%). One‐third of participants were from Europe (30%), most were male (58%), one‐fifth were physical therapists (21%), and over one‐third had been in their profession for 11–20 years (35%). Of 131 statements, consensus was achieved for 71 statements (54%): 53 in agreement (75%) and 18 in disagreement (25%). Conclusion: Although there was consensus for statements for definitions of spinal osteoarthritis that were analogous to definitions of osteoarthritis in appendicular joints, a future definition still needs refinement. Importantly, this Delphi highlighted that a future definition should be considered across a spectrum of structural changes and patient symptoms and expressed on a progressive scale.